PERTUMBUHAN TINGGI DAN DIAMETER TANAMAN CAMPURAN BERUMUR 3 TAHUN PADA DAERAH DATAR DAN LERENG DI LAHAN BEKAS TAMBANG BATUBARA - Herijanto Thamrin (Politeknik Pertanian Negeri Samarinda, 2019)
Reclamation of former mines hereinafter referred to as reclamation is an attempt to repair or reclaim land and vegetation in degraded forest areas as a result of mining and energy business activities in order to function optimally according to With the designation (Permenhut number: 146-Kpts-II-1999). Revegetation is a former mine. This activity is intended to restore, maintain and improve the functions of forests and land so that the carrying capacity, productivity, and role in supporting the life buffer system is maintained (anonymous, 2004). The objectives of the study are to know the height and diameter growth of the Sengon (Paraserianthes falcataria), Sengon Buto (Enterolobium cyclocarpum), Johar (Cassea Siamea) and Trembesi (Samanea Saman) in flat areas and Area of the slope on a former mine and to find out if there is any difference in growth in both conditions of the area. This research was conducted in PT. Khotai Makmur Insan Abadi (KMIA) in Separi village of Tenggarong Seberang district from Kutai Kartanegara Regency for 3 months which is from October to December 2018 conducted in two conditions with the creation of plots namely on a flat area and slope area with a size of 20x20 m each two pieces plot. The research plots are placed intentionally (purposive) to be able to represent the desired location. The measurement of the diameter using phiband and height using the Clinometer is done on the tree that goes inside the plot. The measurement results are processed using simple statistics and to know the difference in the growth used t-test . Based on the results of observation, collection and processing of data, it can be concluded that the plant growth of Sengon (Paraserianthes falcataria), Sengon Buto (Enterolobium cyclocarpum), Johar (Cassea siamea) and Trembesi (Samanea saman) that 3 years old on former land of PT. Khotai Makmur Insan Abadi (KMIA) in Separi village Tenggarong Seberang district the Regency of Kutai Kertanegara relatively equal. Then based on the results of the t-test is obtained there is no difference in plant growth between the slope area and in the flat area. The advice that can be given from this research is the need to be diversified planting distances to get the closure of the ideal vegetation.